Combination Treatment with All-Trans Retinoic Acid Prevents Cisplatin-Induced Enrichment of CD133+ Tumor-Initiating Cells and Reveals Heterogeneity of Cancer Stem Cell Compartment in Lung Cancer. Issue 7 (July 2015) - Moro, Massimo; Bertolini, Giulia; Pastorino, Ugo; Roz, Luca; Sozzi, Gabriella
<x xml:space="preserve">Abstract</x> The existence of specific cellular subpopulations within primary tumors with increased tumorigenic potential and chemotherapy resistance (tumor-initiating cells, TICs) holds great therapeutic implications. Resistant cells can remain quiescent for long periods and be responsible for local relapses and metastasis. We and others have previously described in non–small-cell lung cancer the presence of cisplatin-resistant CD133+ cells with tumor-initiating potential and co-expression of CXCR4 as possible indicator of TICs with disseminating potential. In this study, we report, by in vitro cell fate tracing systems, heterogeneity within the TIC compartment with a highly quiescent pool and a slowly dividing subpopulation, both containing CD133+ cells but respectively enriched for CD133+/CXCR4− and CD133+/CXCR4+ cells. Pretreatment with differentiating agent all-trans retinoic acid counteracts cisplatin resistance specifically of the slowly dividing compartment indicating effect on CD133+/CXCR4+ cells. The same effects are appreciable also in vivo in patient-derived xenografts, where several cycles of all-trans retinoic acid and cisplatin treatment are able to stably reduce this fraction of TICs and tumor dissemination. Thus, partially affecting the heterogeneous TICs compartment, differentiating therapy has promising effects in counteracting cisplatin resistance of CD133+ cells, reducing both local tumor growth and dissemination. In addition, our approach discloses a further level of complexity of chemotherapy-resistant CD133+ TICs, revealing phenotypical and functional heterogeneity of the cancer stem cell compartment in lung cancer.